Analgesic Effects of Low-Dose Ropivacaine for Interscalene Brachial Plexus Block for Outpatient Shoulder Surgery—A Dose-Finding Study. Issue 5 (1st September 2001) - Krone, Susanne C.; Chan, Vincent W.S.; Regan, Joan; Peng, Philip; Poate, Eileen M.; McCartney, Colin; Miniaci, Anthony
Abstract : Background and Objectives: Interscalene brachial plexus block (ISB) with low-dose bupivacaine provides effective postoperative shoulder analgesia in outpatients. The analgesic effect of low-dose ropivacaine for ISB is unknown. Methods: In this double-blind study, 66 outpatients scheduled to undergo arthroscopic shoulder surgery were randomly assigned to receive an ISB with 10 mL of 0.125%, 0.25%, or 0.5% ropivacaine before surgery. Postoperative verbal pain rating score, analgesic consumption, and the extent of motor and sensory block was assessed for 120 minutes after surgery. Results: The degree of shoulder analgesia was dose dependent. Postoperative pain scores were lowest with 0.5% ropivacaine, and analgesic was not required in the hospital in 70% of the patients who received 0.25% and 0.5% ropivacaine, compared to 30% with 0.125% ropivacaine ( P < .03). In the patients who required no analgesic in the hospital, the time to first oral analgesic at home was approximately 10 hours irrespective of ropivacaine concentration. Motor and sensory block distal to the elbow was detected in 25% of the patients in the 0.5% group but none in the 0.125% group. Conclusions: Interscalene brachial plexus block with low-dose ropivacaine, 10 mL of 0.25% and 0.5%, provides effective long-lasting shoulder analgesia in a majority of patients after arthroscopic surgery.